Ramen Chakrabarti
Ramen Chakrabarti talks about the presence of big engineering in the Bay Area when he arrived in 1970 and how the name "Silicon Valley" did not exist then. He talks about seeing the Indian community expand with restaurants, grocery stores, and other Indian-owned businesses. He also speaks about how he and other Bengalis came to form the Prabasi club, of which he was the first president, as well as his involvement in the Sanskriti group where he performed Durga Pujas for the Desi community. In doing so, he brings up his concern for the commercial part of the temple and Durga Puja businesses, as well as the competition of Silicon Valley, and his wish for spirituality to be maintained as a focus.